Brain Lesions as a Predictor of Therapeutic Outcomes of Hand Function in Infants With Unilateral Cerebral Palsy. (December 2018) - Chamudot, Rena; Parush, Shula; Rigbi, Amihai; Gross-Tsur, Varda
Aim: The present study aimed to investigate whether the response variability of infants to modified constraint-induced movement therapy and bimanual therapy are associated with different types of brain lesions. Method: Infants with unilateral cerebral palsy (N = 22) ages 8-15 months (mean = 10.95, standard deviation = 2.15 months) were grouped according to having either a periventricular brain lesion or a middle cerebral artery infarct lesion. Improvement in hand function was analyzed based on the mini–Assistive Hand Assessment results. Results: Infants with periventricular brain lesion displayed greater positive response to upper limb treatment compared to those with middle cerebral artery infarct ( P = .02). A significant difference in improvement according to type of treatment was found in the middle cerebral artery infarct group but not in the periventricular brain lesion. Conclusion: The present study showed an association between the type of brain lesion and the efficacy of upper limb treatment in infants. Infants with periventricular brain lesions displayed greater positive responses than those with middle cerebral artery infarct.